Cuerpo vivido en la experiencia de mujeres con diagnóstico de anorexia o bulimia (2009)
ABSTRACT: This study is a comprehensive approach to the body experience of women diagnosed with anorexia or bulimia. Method: the research was carried out using a qualitative approach and the procedures of phenomenology-hermeneutics; in depth individual interviews and focus groups were used on 15 women who had been diagnosed with the aforementioned disorders. Conclusions: it was found that weighing and sizing systems act as body beauty indicators which anorexic/bulimic women adopt as imperatives for obtaining the body of their wishes. The idea of distortion of body image is discussed since, once affected by these disorders, women may feel fat despite seeing that they are slim. Finally, body experience during treatment is problematized.